Assessing the water quality of canals in Dhaka city, Bangladesh - Rahman, Md. Kholilur; Hossain, Md. Shanawez (Scientific and Academic Publishing, 2022)
This article was published in The American Journal of Environmental Engineering [©2020 The Author(s). Published by Scientific & Academic Publishing] and the definite version is available at: doi:10.5923/j.ajee.20201002.02 The Article's website is at: http://article.sapub.org/10.5923.j.ajee.20201002.02.html